Influência da vinhaça e da palhada de cana-de-açúcar na sorção de herbicidas aplicados em diferentes solos - Matos, Ana Karollyna Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The pr oduction system with or without the straw as how the sugarcane vinasse application may cause some changes in the soil properties and may influence the avaiability of the herbicides in the soil solution. Based on that, the objective of this study was to eva luate the water influence after passing throught the sugarcane straw and the vinasse, both correlated with the availability of the herbicides a micarbazone, clomazone, diuron, hexazinone, imazapc, sufentrazone and tebuthiuron in the soil solution in differ ent kinds of soils. The factorial 3 x 31 with complete randomized block design, with three replications, was used with 31 physical and chemical different soil samples and three treatments (water, wash water straw and vinasse). The soil samples were arrange d on trays and submitted to the herbicides application, then they were placed in plastic cartridges and satured with deionized water, wash water straw and vinasse, and remained resting for 18 hours under refrigeration (8 ± 3 o C) . After that, two extrations were made: the first one quantifying the presence of the herbicides in the soil solution and in the second one the total extraction of herbicide remaining in the soil was taken to determine the recovery percentage of each herbicide tested. For quantificat ions it was used a LC - MS/MS system, compound of a High Performance Liquid Chromatograph (HPLC) coupled with mass spectrometer. The amicarbazone and imazapic herbicides, in most samples, were more available in the soil solution with the water application an d in the wash water straw. However, vinasse had promoted an increase availability of diuron and tebuthiuron in all soils. Clomazone, hexazinone and sulfentrazone showed no significative difference between the treatments. The herbicides with the highest fre quency of availability of herbicides in soils were imazapic, hexazinone, amicarbazone and tebuthiuron. However, about 6% of ...

O sistema de produção com ou sem a pres ença de palhada, bem como, a aplicação de vinhaça nos canaviais, podem levar a alterações nas propriedades do solo e influenciar a disponibilidade dos herbicidas na solução do solo. Diante disto, o presente trabalho teve por objetivo avaliar a influência d a água, água após passar pela palha de cana - de - açúcar e vinhaça na disponibilidade na solução do solo dos herbicidas amicarbazone, clomazone, diuron, hexazinone, imazapic, sulfentrazone e tebuthiuron em diferentes solos. Adotou - se o esquema fatorial 3 x 31, com delineamento em blocos inteiramente casualizados com três repetições, sendo utilizadas 31 amostras de solos distintos quanto às características físicas e químicas e três tratamentos (água, água de lavagem de palha e vinhaça). As amostras de solo foram dispostas em bandejas e submetidas à aplicação dos herbicidas, em seguida foram acondicionadas em cartuchos plásticos e saturadas com água deionizada, água de lavagem de palha e vinhaça, permanecendo em repouso durante 18 horas sob refrigeração (8 ± 3 ° C) . Posteriormente, fez - se duas extrações, na primeira quantificou - se os herbicidas presentes na solução do solo e na segunda foi realizada a extração total do herbicida remanescente no solo para determinação da porcentagem de recuperação de cada herbicida t estado. Para as quantificações utilizou - se um sistema LC - MS/MS, composto por um Cromatógrafo Líquido de Alta Performance (HPLC) acoplado ao espectrômetro de massas. O amicarbazone e o imazapic foram mais 2 disponibilizados na solução dos solos com a aplicaçã o de água e água de lavagem de palha na maioria das amostras. Todavia, a adição de vinhaça promoveu uma maior disponibilização do diuron e tebuthiuron em todos os solos. O clomazone, hexazinone e sulfentrazone não apresentaram diferença significativa entre os ...
Keywords: Cromatografia liquida; Herbicidas; Adsorção; Liquid chromatography